Identification and expression of differentially expressed genes in the hard clam, Mercenaria mercenaria, in response to quahog parasite unknown (QPX) - Allam Bassem; Tanguy Arnaud; Perrigault Mickael (BMC Genomics, 2009)
Abstract Background The hard clam, Mercenaria mercenaria, has been affected by severe mortality episodes associated with the protistan parasite QPX (Quahog Parasite Unknown) for several years. Despite the commercial importance of hard clams in the United States, molecular bases of defense mechanisms in M. mercenaria, especially during QPX infection, remain unknown. Results Our study used suppression subtractive hybridization (SSH), as well as the construction of cDNA libraries from hemocytes to identify genes related to the defense of the hard clam against its parasite. Hard clams were experimentally infected with QPX and SSH was performed on mRNA samples extracted from mantle and gill tissues at different times post-challenge. A total of 298 clones from SSH libraries and 1352 clones from cDNA libraries were sequenced. Among these sequences, homologies with genes involved in different physiological processes related to signal transduction, stress response, immunity and protein synthesis were identified. Quantitative PCR revealed significant changes in the expression of several of these genes in response to QPX challenge and demonstrated significant correlations in terms of levels of gene expression between intermediates of signalling pathways and humoral defense factors, such as big defensin and lysozyme. Conclusion Results of this study allowed the detection of modifications caused by QPX at the transcriptional level providing insight into clam immune response to the infection. These investigations permitted the identification of candidate genes and pathways for further analyses of biological bases of clam resistance to QPX allowing for a better understanding of bivalve immunity in general.